Visual-vestibular motion cueing assessment in maritime rotorcraft flight simulators - Memon, W.A.; White, M.D.; Owen, I. (My University, 2019)
Confidence in the Modelling and Simulation (M&S) tools used in flight simulators depends upon the identification of the fidelity requirements for a particular application. The critical M&S elements integrated into the helicopter-ship dynamic interface simulation environment are motion and visual cueing, the flight dynamics model, unsteady ship’s airwake and deck motion. The paper reports the results of a piloted flight simulation experiment conducted in a full-motion simulator, to study the effects of varying the visual and vestibular motion cueing fidelity on the pilot’s perception, task performance and workload. Three different motion tuning sets were tested in three visual cueing scenarios for a representative SH-60B ‘Seahawk’ helicopter landing on a naval single-spot destroyer at different wind and sea-state conditions. It was found that when high-fidelity vestibular motion was provided to the pilot, the dependency on the visuals to capture aircraft state information was reduced. Similarly, when the high-fidelity visual cueing was provided, the pilot perceived balanced and synchronised overall motion cues leading to reduced workload and improved task performance. Moreover, the individual and combined effect of visual-vestibular fidelity was found to be more noticeable at higher wind and sea conditions, for which an ‘Optimised’ vestibular motion tuning set and a High Visual Cueing scenario combination was obtained, this led to reduced pilot workload and improved simulated maritime helicopter operational capability.